PENGELOLAAN SEKTOR PERIKANAN TANGKAP MENURUT EKONOMI ISLAM DAN PEMBANGUNAN BERKELANJUTAN - Angga Prasetya Anugrah; Ida Busneti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This study aims to analyze the condition of capture fisheries in Indonesia, the role of government in the management of capture fisheries, as well as the Islamic view of capture management in Indonesia. The method used is descriptive analysis with a literature study approach with variables consisting of capture fisheries, government policies, management, sustainable development, and Islamic perspectives. The results of this study are that the capture fisheries environment in Indonesia is in critical condition, but the potential of Indonesian fisheries is still quite large. The role of the government in fishing management is to crack down on fisheries IUU (Illegal, Unreported, and Unregulated), prohibiting the use of fishing gear that damage the environment, and setting limits on catch size for certain marine species. In an Islamic perspective, the government in managing fisheries resources is in accordance with Islamic teachings, due to the prohibition of exploitative actions, damaging the environment, and managing the environment so that it is renewable and sustainable.